Pelatihan Seni Kolase sebagai Upaya Peningkatan Kreativitas Visual Anak Usia Dini di MIN 2 Kota Palangka Raya - Imron, Muhammad; Hairil, Muhammad; Mahmudah, Istiyati (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service aims to enhance the visual creativity of early childhood children through collage art activities at MIN 2 Kota Palangka Raya. In the current digital era, children are often exposed to passive visual media, which can hinder the development of their active creativity. Through the collage art approach, students are given the freedom to create using various materials such as colored paper, origami, and glue, which stimulate fine motor skills and visual creativity. The research method used involved direct guidance in creating collages, followed by the presentation of material about collage art and the steps for creating it. The results of the community service show that collage activities can improve students' creativity, visual expression, and fine motor skills. Additionally, these activities can also boost students' self-confidence in expressing themselves freely and creatively. These findings suggest that collage art can serve as an effective medium in art education at the elementary school level and is highly beneficial for fostering children's creativity from an early age.